THE INFLUENCE OF THE NEW GROWTH REGULATOR BIOGLOBIN ON THE YIELD AND QUALITY OF ROOT PARSLEY - Dydiv І.; Dydiv О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
One of the important factors in increasing the yield of vegetable crops is the use of plant growth regulators. This is especially relevant in conditions of moisture deficit, which has often been manifested in recent years. The use of modern growth regulators helps to increase the yield and quality indicators of vegetable products, in particular root parsley. The article highlights the results of research on the influence of the domestic ecologically safe growth regulator Bioglobin on the productivity and quality of root crops of parsley of the Dutch selection of the Igl variety. Growth regulator Bioglobin was used in the form of a starting solution for the treatment of seeds and leaf surfaces of plants. The obtained research results confirm that when growing parsley on ridges, seed treatment with Bioglobin (0.5 l/t) + foliar fertilization in three terms contributed to the best increase in the mass of parsley root crops (154 g) and the largest increase (42 g, or 37.5 %) compared to the control (112 g). Foliar top dressing with Bioglobin (0.5 l/t) in three terms reduced the average weight of parsley root crops to 141 g, and when only seeds were treated with Bioglobin, the average weight of root crops was 123 g. Research has established that the highest yield of parsley root crops (39.4 t/ha) was obtained in the variant when the growth regulator Bioglobin was used both for seed treatment and for foliar fertilization in three terms. The increase to the control (without treatment) was 10.8 t/ha or 37.7 %. The highest yield of marketable parsley roots (92 %) was obtained by treating seeds with Bioglobin (0.5 l/ha) + foliar feeding in three terms. The growth regulator Bioglobin had a positive effect on increasing the qualitative biochemical indicators of parsley roots. A high content of dry matter (23.7 and 23.3 %) was observed after foliar feeding with Bioglobin (0.5 l/t) in two terms during the period of intensive growth of root crops. The highest content of the sum of sugar (4.9 %) and vitamin C (48.3 mg/100 g) in root crops was established after seed treatment with Bioglobin (0.5 l/t) + foliar feeding in three terms, which is higher than the control by 1.0 % and 12.9 mg/100g. The studies revealed a tendency to decrease the concentration of nitrates in parsley root crops with an increase in the number of treatments with the growth regulator Bioglobin, however, in all variants of the experiment, the nitrate content did not exceed the MPC.